Forgotten “young lions”: Stories of political activists in the struggle against apartheid - Langa, Malose (PINS-Psychology in Society, 2016)
Reynolds, Pamela (2014) War in Worcester: Youth and the Apartheid state. Pietermaritzburg: UKZN Press. ISBN 978 1 86914 276 6 pbk. Pages 239.